1998
DOI: 10.1002/(sici)1099-0844(199803)16:1<51::aid-cbf767>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Inositolphosphoglycans possibly mediate the effects of glucagon-like peptide-1(7-36)amide on rat liver and adipose tissue

Abstract: Insulin-like effects of glucagon-like peptide-1(7-36)amide (GLP-1) in rat liver, skeletal muscle and fat, and also the presence of GLP-1 receptors in these extrapancreatic tissues, have been documented. In skeletal muscle and liver, the action of GLP-1 is not associated with an activation of adenylate cyclase, and in cultured murine myocytes and hepatoma cell lines, it was found that GLP-1 provokes the generation of inositolphosphoglycan molecules (IPGs), which are considered second messengers of insulin actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…GLP-1, an incretin with insulinotropic and insulin-independent anti-diabetic properties (Creutzfeldt 2001), exerts insulin-3-like effects upon glucose metabolism in the liver, the skeletal muscle, and fat, apparently through a specific receptor different from that cloned in the pancreas (Valverde et al 1994, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995, Yang et al 1998, Villanueva-Peñacarrillo et al 2001b, Sancho et al 2005, Arnés et al 2008. In adipose tissue, GLP-1 has opposite actions upon lipid metabolism -lipogenic and lipolytic -which are mediated by cAMP and inositolphosphoglycan (IPG) signaling pathways respectively (Ruiz-Grande et al 1992, Márquez et al 1998, Villanueva-Peñacarrillo et al 2001a. Ex-4 is a natural occurring non-mammalian peptide that shows partial homology to GLP-1 and shares with this incretin several glucose and lipid regulatory effects in both normal and diabetic states (Eng et al 1992).…”
Section: Introductionsupporting
confidence: 68%
“…GLP-1, an incretin with insulinotropic and insulin-independent anti-diabetic properties (Creutzfeldt 2001), exerts insulin-3-like effects upon glucose metabolism in the liver, the skeletal muscle, and fat, apparently through a specific receptor different from that cloned in the pancreas (Valverde et al 1994, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995, Yang et al 1998, Villanueva-Peñacarrillo et al 2001b, Sancho et al 2005, Arnés et al 2008. In adipose tissue, GLP-1 has opposite actions upon lipid metabolism -lipogenic and lipolytic -which are mediated by cAMP and inositolphosphoglycan (IPG) signaling pathways respectively (Ruiz-Grande et al 1992, Márquez et al 1998, Villanueva-Peñacarrillo et al 2001a. Ex-4 is a natural occurring non-mammalian peptide that shows partial homology to GLP-1 and shares with this incretin several glucose and lipid regulatory effects in both normal and diabetic states (Eng et al 1992).…”
Section: Introductionsupporting
confidence: 68%
“…In these cells, GLP-1, like insulin, induced the immediate hydrolysis of GPIsindicating the generation of IPGs -with a global dynamic similar to that previously detected not only in BC3H-1 myocytes (Galera et al 1996) but also in a hepatoma cell line (Trapote et al 1996) and in rat hepatocytes and adipocytes (Márquez et al 1998), suggesting a role for IPGs in the immediate post-receptor mechanism leading to the GLP-1 actions.…”
Section: Discussionmentioning
confidence: 99%
“…Primary culture myocytes (2 10 4 cells per well) from each subject were pre-labeled, for 60 min at 37 C, with 0·2 µCi myo-[ 3 H]inositol in 0·75 ml -MEM with added 0·1% BSA, 1% glutamine and 1% antibiotics; the radioactive medium was then removed and cells were incubated in fresh -MEM for different time periods (0·5-10 min) in the absence (control) and presence of peptides. Incubation was interrupted by addition of 10% TCA at 4 C, and the radioactive GPI content was extracted and determined in the respective precipitates, as previously described in detail (Márquez et al 1998).…”
Section: Ipgsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these extrapancreatic tissues, GLP-1 seems to act through specific receptors (Mérida et al 1993, Valverde et al 1993, Delgado et al 1995, Villanueva-Peñacarrillo et al 1995a,b, Yang et al 1998 which, unlike the pancreatic one (Thorens 1992), are not associated with an activation of adenylate cyclase , Yang et al 1998. It has been proposed that an inositol phosphoglycan (IPG) could be one of the possible second messengers in the actions of this peptide (Galera et al 1996, Trapote et al 1996, Márquez et al 1998. In fact, a recent report has shown that GLP-1 stimulates glycogen synthase a activity and glycogen synthesis in human skeletal muscle strips and primary culture myotubes, as does insulin, and that it fails to modify the cellular cAMP content while stimulating IPG generation (Luque et al 2002).…”
Section: Introductionmentioning
confidence: 99%